UNDERPRICING SIGNALS: EXPLOITATION OF DAR VARIABLES (DEBT TO ASSET RATIO) - Jufri Yandes (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The analysis of DAR (Debt to Asset Ratio) associated with the level of underpricing movement is the main focus in this study process. This study adopts a quantitative approach and relies on secondary data with a focus on explanatory research. The utilisation of purposive sampling method in sample selection allows the study to focus on 77 issuers over a significant period from 2021 to 2022. The uniqueness of this study lies in the use of the latest data and a sample that reflects the situation during the period. In analysing the data, linear regression with the support of EViews software is used as the main tool to test the hypothesis. The data source is obtained from the information of companies conducting initial public offerings and accessed through the Indonesia Stock Exchange website. The calculation results show a significant impact of the DAR variable on the level of movement of IPO stock underpricing. The positive coefficient on the DAR variable indicates that an increase in the DAR value has the potential to increase the level of movement of IPO stock underpricing, and vice versa.